2014
DOI: 10.1002/pbc.25363
|View full text |Cite
|
Sign up to set email alerts
|

Detection of central nervous system involvement in childhood acute lymphoblastic leukemia by cytomorphology and flow cytometry of the cerebrospinal fluid

Abstract: FCI of the CSF increased the detection rate of CNS involvement of ALL approximately two times compared to cytomorphology. Patients with low-level CNS involvement may benefit from additional intensified systemic or CNS-directed therapy, but larger studies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
58
1
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 29 publications
3
58
1
7
Order By: Relevance
“…All but two patients with facial palsy and one of the three patients with hearing loss who underwent imaging had findings consistent with CNS involvement. In concordance with previous studies, 5,18 we found that patients with cranial nerve palsy rarely had leukemic cells in the CSF and MRI may be a useful addition in diagnosis of these patients.…”
Section: Discussionsupporting
confidence: 92%
“…All but two patients with facial palsy and one of the three patients with hearing loss who underwent imaging had findings consistent with CNS involvement. In concordance with previous studies, 5,18 we found that patients with cranial nerve palsy rarely had leukemic cells in the CSF and MRI may be a useful addition in diagnosis of these patients.…”
Section: Discussionsupporting
confidence: 92%
“…No evidence from our SR informed this statement; however, evidence identified outside our SR indicated that flow cytometry can effectively detect disease in CSF samples from patients with ALL 261,262 and can detect subtle leukemic involvement in some cytologically negative CSF samples from both pediatric and adult patients with B-ALL and T-ALL. 263,264 Moreover, patients with ALL and CSF disease not detected by visual inspection of cytocentrifuge preparations but detectable by flow cytometry involvement have shorter OS times than do those with no involvement detected by flow cytometry (P ¼ .01 on multivariate analysis).…”
mentioning
confidence: 75%
“…A total of 41 studies comparing flow cytometry and cytology in CSF samples from patients with lymphoid neoplasia were identified .…”
Section: Resultsmentioning
confidence: 99%
“…47 Regarding study populations, 17/27 include only proven hematological diagnoses with risk factors or signs/symptoms suggestive for CNS dissemination, whereas 2/27 comprise a mixture of proven and suspected hematological diagnoses. Moreover, 6/27 comprise only cases of acute lymphoblastic leukemia/lymphoma 8,17,25,[28][29][30] and 2/27 encompass only cases of T-cell lymphoma. 24,32 Analytical informations are summarized in Table III.…”
Section: Resultsmentioning
confidence: 99%